Self Efficacy of Pre-Service English Teachers in Using English as a Language Instruction - Adria Rosy Starinne; Dyah Kurniawati (Universitas Muhammadiyah Gresik, 2019)
Field Experience Program or Praktek Pengalaman Lapangan (PPL) are carried out by students to fulfill the requirements for the formation of the education profession. But in the process of PPL, the pre-service English teachers of English Language Education Study Program at the University of PGRI Ronggolawe Tuban often experience problems related to their efficacy when teaching in English as language of instruction.This study aims to determine the efficacy of English Language Education students who run the Field Experience Program (PPL) in using English as the language of instruction, as well as what factors influence their efficacy in using English as the language of instruction. It is a phenomenological qualitative research which the choice of subject or data source was done by purposive sampling which focused on selected informants who were appropriate for in-depth studies (Nana Syaodih, 2007: 101). The subjects are pre-service English teachers who had finished undergoing PPL in the period between November 2017 to January 2018. Data collection techniques used are observation, interviews, and documentation, and using descriptive inductive analysis.The results of this study reveal that self-efficacy of all pre-service English teachers (six students) as subjects in this study in terms of the use of English as the language of instruction during PPL has varied self-efficacy on dimensions of magnitude, strength and generality. Only 1 out of 6 students had negative self-efficacy in all dimensions, and 1 (one) person showed positive self-efficacy in all dimensions; magnitude, strength and generality. While the others vary for all three dimensions. Those six students used both English and Indonesian in teaching English. The reason was because they were not confident (2 people), and for the emphasis on certain material delivered so that it is more easily understood (4 people).This study found that the factors of success experience and psychological factors were the strongest in forming self-efficacy of the 6 PPL pre-service teachers in using English as the language of instruction during field experience program. Furthermore, it is only slightly influenced by other people's success factors and social persuasion. The more experience and the better the psychological condition of students, the more positive their self-efficacy. Two students, namely Mg and Su, have negative self-efficacy due to the lack of teaching experience and poor psychological conditions because they felt uncomfortable and underappreciated in the school where they carried out the field experience program.